Postcolonial Hermeneutics: Concepts and Contribution to Understanding Socio-Religious Problems in Southeast Asia - Novita Dewi (Center for Southeast Asian Social Studies (CESASS), 2018)
Scrutiny of unequal power-relations between the “East” and the “West” in politics, culture, economy, and various aspects of life is the concern of postcolonial studies. Foucault's concept of power is central in postcolonial theory with which Edward Said is celebrated for his dismantling of Orientalist views. Postcolonial literature, likewise, has contributed to the growth and development of postcolonial criticism. The first objective of this article is to give a brief overview of different terms attached to the word “postcolonial”, i.e. postcolonial literary criticism, postcolonial literature and postcolonial theory, since these terms enrich one another theoretically. The second objective is to discuss postcolonial hermeneutics as a reading tool to examine various mundane practices in Southeast Asian postcolonial society. The purpose is to achieve a balanced, reciprocal exchange of perspectives while providing legitimacy for alternative interpretations to the hegemony shown in “Western” discourse. Citing traditional ways of conflict resolution and eco-friendly land management as examples, this article concludes that postcolonial reading may shed light on how socio-religious conflicts, hybrid experiences of faiths, and other social practices operate and get their respective meanings in postcolonial countries across Southeast Asia.